Developing a Business Model for Beginner Entrepreneurs for “Simalungun Maju” - Tua Siregar, Robert; Ekana Nainggolan, Lora; Triapnita Nainggolan, Nana; Sjafei Purba, Djuli; O.P. Damanik, Elfina; Siregar, Junifer (CV. Inara, 2025)
In the era of globalization and rapidly changing technology, the role of entrepreneurship is increasingly important to create innovation, create jobs, develop infrastructure, and improve people's welfare. In the Indonesian economy, entrepreneurship can be one of the answers to encourage economic growth. This is because the economy of the Republic of Indonesia is now in the shadow of weakening purchasing power, which is influenced by rising interest rates and high inflation. For this reason, by continuing to increase entrepreneurship through the right policies and a conducive business environment, it is hoped that employment will be more wide-open, increase people's income and ultimately contribute to public consumption, thereby promoting sustainable and inclusive economic growth in Indonesia. This is the basis for community service activities in the form of business model development training for beginner entrepreneurs to be carried out. Located in three different sub-districts in Simalungun Regency, namely Bandar, Bosar Maligas and Bandar Masilam Districts, with the target of getting participants who will later be included in the advanced fostered members.